"The Role of Entrepreneurial Networking in Entrepreneurial Change A Study of a Sample of Private Universities in Kurdistan Region, Iraq" - Aldawod, Alvin (The Arab Journal of Administration, 2022)
This study aims to identify the correlation and effect between entrepreneurial networking and entrepreneurial change in a number of private universities in the Kurdistan Region – Iraq. Inductive reasoning was followed to conduct the present study, which depends on the questionnaire as the main technique to collect data. To achieve the research aim, two hypotheses were developed: the first indicates that there is a significant correlation between entrepreneurial networking types and entrepreneurial change; the second indicates that entrepreneurial networking significantly impact on the entrepreneurial change. Using a non-random sample technique, the questionnaire was distributed to managerial leaders in the universities under study; fifty-one questionnaires were valid for the analysis. The study used a group of statistical tools to analyze data by employing the (SPSS) package. The results of the descriptive analysis indicated that there is an acceptable agreement among respondents on the availability of the types of entrepreneurial networking and dimensions entrepreneurial change in the universities considered. The findings show that there is entrepreneurial networking (represented by social networks, business-focused networks, and inter-organizational strategic networks) in the considered universities contributes to bringing about entrepreneurial change that requires entrepreneurial innovation, transformational change, and disruptive strategies.In light of the results of the present study, the researcher suggests that the considered universities need to strengthen their entrepreneurial networks and benefit well from the social, business, or strategic relationships they have with other organizations. Also, they need to make the most of these networks, because that will not only help them in making the required entrepreneurial change, but in many other aspects, such as adapting to the rapidly changing environment, seizing opportunities, obtaining more resources, and achieving a better performance